Assurance of the Function of Low-Volume Roads for the Improvement of Driving Conditions - Viktoras Vorobjovas (The Baltic Journal of Road and Bridge Engineering)
This summary of the author’s PhD thesis supervised by Assoc Prof Dr Daiva Žilionienė and defended on 21 January 2011 at the Vilnius Gediminas Technical University. The thesis is written in Lithuanian and is available from the author upon request. Chapter 1 gives the analysis of road classifications in Europe and other countries of the world, the development of road classification in Lithuania, also the sustainable safety principles and driving conditions on lowvolume roads the aim and tasks of the work are formulated. Chapter 2 presents analysis of road alignment elements and road structure elements, also their influence on driving conditions and visibility. Chapter 3 describes methodology of experimental research aimed to determine, analyze and model the quality of the existing low-volume road alignment, parameters of road structures and characteristics of road pavements. Chapter 4 gives data obtained by the experimental research, data analysis, evaluation and the models for the improvement of driving conditions in designing and reconstructing low-volume roads.